Leap : How to Survive and Thrive in the Sustainable Economy - Turner, Chris, 1973- (Book collections on Project MUSE., 2012)
The crises in our economic system, our energy supply, and our climate are converging. Solving these crises requires a fundamental change in our frame of reference--a decisive shift not so much in technology as in technique. In The Leap, award-winning journalist Chris Turner presents a field guide to making the jump from our current system of energy supply and consumption to a sustainable model that succeeds across the socioeconomic spectrum. It is an integrated approach, one that he calls a "great leap sideways," because it is a lateral leap that anyone can make: not escaping from, but moving toward.